Pengaruh Proporsi Saham Publik Terhadap Kinerja Perusahaan : Studi Kasus Pada Perusahaan Yang Terdaftar Di Bursa Efek Jakarta - Purba, Jan Horas Veriyadi (Jurnal Ilmiah Ranggagading (JIR), 2004)
The goals of this research is to find out correlation between public share ownership proportion with firm performance and to find out the influence of public share to firmâs performance (ROI). Correlational analysis was done by means of contingency table, and statistics test is Chi square. Rate Chi square is 2290,067, whereas statistics test rate with alpha 0.05 and degree of freedom 16 is 26,296. Thereb, it could be concluded that there is positive and significant correlation between public share proportion with firmâs performance at firm registered at Jakarta Stock Exchange. Punlic share proportion has unequal influence to firmâs performance. If public share is less than 40%, to be found out result that public share does not have positive and significant influence to firmâs performance. Whereas, if public share proportion reaches 40% or more, regression analysis result shows positive influence. Public share proportion variable has positive influence to ROI. It means, if public share proportion at firm increases, firmâs degree of ROI will be higher too. This one reflects the greater public share proportion share the better firmâs performance (ROI). If public share ownership rises 1%, ROI will rises 0,833%. By t test, to be obtained rate of t stat. For regression coefficient as 6,559, whereas tÎ±/2; 114 = 1,981. Thereby, public share proportion variable as presented above has significant influence to firmâs performance (ROI). Keywords : Public Sare Proportion; Firmâs Performance.